2009
DOI: 10.1063/1.3112025
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring carbon nanotips in the plasma-assisted chemical vapor deposition: Effect of the process parameters

Abstract: Carbon nanotips have been synthesized from a thin carbon film deposited on silicon by bias-enhanced hot filament chemical vapor deposition under different process parameters. The results of scanning electron microscopy indicate that high-quality carbon nanotips can only be obtained under conditions when the ion flux is effectively drawn from the plasma sustained in a CH4+NH3+H2 gas mixture. It is shown that the morphology of the carbon nanotips can be controlled by varying the process parameters such as the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The details of the deposition system and its operation can be found elsewhere [27]. Briefly, the reactor contains three coiled hot tungsten filaments for feedstock gas heating and pre-ionization.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the deposition system and its operation can be found elsewhere [27]. Briefly, the reactor contains three coiled hot tungsten filaments for feedstock gas heating and pre-ionization.…”
Section: Methodsmentioning
confidence: 99%
“…When these ions bombard with the carbon film, the etching ions play a role in sputtering-etching of the carbon film deposited on silicon substrate, while the carbonaceous ions play a role in carbon deposition. In the previous work, we studied the formation of carbon nanotips from carbon film [16] and concluded that the formation of carbon nanotips resulted from the dynamic equilibrium of sputteringetching of etching ions and deposition of carbonaceous ions on the both sides of microhillocks formed on the carbon film. In this experiment, it was found that the different temperatures can result in the formation of carbon nanotips and nanotubes.…”
Section: Formation Of Carbon Nanotips and Carbon Nanotubes Depending mentioning
confidence: 99%
“…1 and 2 indicate that the carbon nanotips and nanotubes are grown from carbon film depending on temperature, which are related to the ion bombardment and diffusion at different temperatures. During the growth of carbon nanotips and nanotubes, the reactive gases are ionized by plasma into the carbonaceous ions (such as CH 3 + , CH 2 + ) and the etching ions including nitrogenous and hydrogen ions (such as N + , NH + , H + ) [4,16]. When these ions bombard with the carbon film, the etching ions play a role in sputtering-etching of the carbon film deposited on silicon substrate, while the carbonaceous ions play a role in carbon deposition.…”
Section: Formation Of Carbon Nanotips and Carbon Nanotubes Depending mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, nitrogen-based ions N þ 2 , NH þ 2 , NH þ 3 , and NH þ 4 are produced in the plasma, and these ions can significantly sputter the surface of NCNTPs. 27,28 Moreover, the sputtering yield increases with the increase of the energy and mass of the impinging nitrogen-based ions. 29,30 As shown in Table I, the bias remained almost unchanged during the growth of samples B and C. However, the increase of nitrogen flow rate and the reduction of hydrogen flow rate result in the change in the partial pressure and the mean free path of the ions.…”
Section: A Structural Analysis Of the Ncntpsmentioning
confidence: 99%